Intellectual property rights management in developing countries - Nyatlo, Sheila Mavis; Caballero, Catherina; Fernando, M. A. M.; Centre for Science and Technology of the Non-Aligned and Other Developing Countries (New Delhi : Daya Pub. House, 2012)
Papers presented at the International Advanced Training Course on Intellectual Property Rights (IPR) for NAM and Other Developing Countries, held at New Delhi and Manesar during, 12-17 July 2010.
Section 1. African continent -- section 2. American continent -- section 3. Asian continent.
"Centre for Science & Technology of the Non-Aligned and other Developing Countries (NAM S&T Centre)."
Includes bibliographical references.
SoL
Trim Education
Keywords: Intellectual property -- Developing countries; Law